Boosting Efficiency of Non‐Fullerene Organic Solar Cells Via Introducing Multidimensional Second Acceptors. Issue 9 (28th June 2022) - Chen, Yan; Hu, Lin; Chen, Na; Wang, Li-Hong; Ye, Dong-Nai; Liu, Hui; Jin, Yingzhi; Li, Zaifang; Liu, Shi-Yong
Abstract : The active layer bulk heterojunction (BHJ) blends with a suitable phase separation and crystallization are of great importance to the exciton dissociation, charge transfer, and ultimately the efficiency of the organic solar cells (OSCs). Herein, an effective approach is developed to modulate the molecule's crystallization and phase separation of BHJ blends via introducing a multidimensional (MD) second acceptor. The efficiency of the OSCs can be largely boosted when the cross‐shaped MD acceptors are introduced into the BHJs as a third component. The ternary OSCs based on PTB7‐Th:IEICO‐4F:SFCPDT exhibit a higher power conversion efficiency (PCE) (PCE = 13.29%) than that of the PTB7‐Th:IEICO‐4F binary system (PCE = 11.67%). It is found that the ternary films deliver higher and more balanced carrier mobility, as well as reduced carrier recombination. The positive effect can be also extended to the PBDB‐T‐2F: IT‐4F‐based ternary system. When FLIDT and SFIDT are employed as the third component, the PCE values can be increased from pristine 11.98–12.42% and 13.16%, respectively. It is anticipated to further boost the efficiency of the non‐fullerene OSCs by rationally designing the structure of the third component for a state‐of‐the‐art active layer system. Abstract : A series of novel acceptors with multidimensional conformation molecular structures (linear or cross‐shaped) are designed and introduced as a third component to effectively modulate the phase separation and inhibit the excessive crystallization of the active layer blend films.